Photoconductivity and nonlinear optical features of novel AgxGaxGe1-xSe2 crystals. (January 2017) - Krymus, A.S.; Myronchuk, G.L.; Parasyuk, O.V.; Lakshminarayana, G.; Fedorchuk, A.O.; El-Naggar, A.; Albassam, A.; Kityk, I.V.
Graphical abstract: Highlights: Complex photoelectrical and nonlinear optical studies are done in Ag – chalcogenides. The correlation between third harmonic generation and the two-photon absorption is established. Principal role of the photoexcited intrinsic defects is shown. Abstract: Complex studies of photoconductivity, two-photon absorption (TPA) and third harmonic generation (THG) were performed for three principal representatives of chalcogenide crystals. Comparison of carrier transport kinetics and third order nonlinear optical properties was performed and the principal role of the anionic co-ordination is discussed. Specific features of photoconductivity in synthesized crystals show that the relaxation kinetics of photoconductivity can be determined by the existence of at least two types of relaxation processes: slow and quick. The control of the relaxation processes for s- and r-centres was carried out by temperature dependences of t-levels relaxation photoconductivity. The maximum THG is observed for the sample AgGaGe5 Se12 . The less THG exists for the sample AgGaGe3 Se8 and the lowest for the AgGaGe4 Se10 .